"Essential Piaget. / ed. by Gruber, Howard E. and Voneche, J. Jacques" - "Gruber, Howard E.(ed.)" (London, 1977)
In this anthology we attempt to compress Jean Piaget's life work into one volume, a task formidable enough simply because of the magnitude of Piaget's oeuvre- over fifty books and monographs and hundreds of articles, published over a seventy-year period. This time scale compounds the problem of selection, since Piaget revisited certain problems several times. If, in the interest of brevity, we include only the latest statement as representing Piaget's final position on the subject, we commit two errors.
Keywords: Child psychology